Hierarchy of Indonesian History Subjects in the Implementation of the Independent Curriculum - ., Bahri; Dewi Riang Tati, Andi; ., Fadli; Manda, Darman; Idrus Al Islami, Achmad (KnE Social Sciences, 2024)
A nation can be built on the foundation of its education. The quality of an education reveals the progress and decline of a country. A country that has a strong educational foundation will also be able to create superior and globally competitive human resources. However, considering the changes in the character of students who continue to move dynamically following the times, the Ministry of Education and Culture initiated the 2013 Independent Curriculum. A question that arises is the position of history education in the independent curriculum. The current study uses a descriptive causative research method to describe data that have been collected without any intention of making generalized conclusions. The result of this study is the impact on teachers of history subjects related to reducing the number of lesson hours, but the solution adopted is to coordinate P5 (Pancasila student profile strengthening project) as a substitute for reduced hours. As for students, more emphasis is given on contextual learning that is close to the real life of students in order to create meaningful learning. Keywords: Indonesian history, independent crriculum